Perbandingan Kewenangan Badan Legislatif di Indonesia dan Amerika Serikat (Perspektif Pembuatan Undang-Undang) - Widya Utami (Staatsrecht: Jurnal Hukum Kenegaraan dan Politik Islam, 2024)
The legislative body, which has the right to formulate and make laws, in Indonesia is the House of Representatives (DPR). Whereas in the United States, the legislative body is the Congress, which consists of the Senate and the House of Representatives. This difference in structure shows that there are many major differences between the structures and functions of the two countries, especially in the area of lawmaking. This difference has an impact on the lawmaking process in each country. This article uses a qualitative method with library research techniques to compare the legislative systems of Indonesia and the United States, especially in the institutional structure and lawmaking process. Data was collected from various literatures such as books, scientific journals, laws and regulations, as well as official documents from the legislative institutions of both countries. This article concludes that the Indonesian Parliament and the United States Congress both have the task of making laws.  In Indonesia, bills can be proposed by the government, members of the DPR, or the public. After being discussed and approved by the DPR, the bill is sent to the president for approval. In the United States, the process is more complicated because it involves two institutions: The Senate and the House of Representatives. Both must approve bills before they are submitted to the president. Members of the Indonesian House of Representatives are elected every five years, while members of the US Congress have different terms: senators are elected every six years and members of the House of Representatives every two years. The legislative process in Indonesia is conducted through discussions in committees before being decided in a plenary meeting.   Abstrak: Lembaga legislatif, yang berhak merumuskan dan membuat undang-undang, di Indonesia adalah Dewan Perwakilan Rakyat (DPR). Sedangkan di Amerika Serikat, lembaga legislatifnya adalah Kongres, yang terdiri dari Senat dan Dewan Perwakilan Rakyat. Perbedaan struktur ini menunjukkan ada banyak perbedaan besar antara struktur dan fungsi dari kedua negara, khususnya pada bidang pembuat undang-undang. Perbedaan ini berdampak pada proses pembuatan undang-undang di setiap negara. Artikel ini menggunakan metode kualitatif dengan teknik studi kepustakaan (library research) untuk membandingkan sistem legislatif Indonesia dan Amerika Serikat, terutama dalam struktur kelembagaan dan proses pembentukan undang-undang. Data dikumpulkan dari berbagai literatur seperti buku, jurnal ilmiah, peraturan perundang-undangan, serta dokumen resmi dari lembaga legislatif kedua negara. Artikel ini menyimpulkan bahwa DPR Indonesia dan Kongres Amerika Serikat sama-sama memiliki tugas membuat undang-undang. Di Indonesia, Rancangan Undang-Undang (RUU) bisa diajukan oleh pemerintah, anggota DPR, atau masyarakat. Setelah dibahas dan disetujui DPR, RUU dikirim ke presiden untuk disahkan. Di Amerika Serikat, prosesnya lebih rumit karena melibatkan dua lembaga: Senat dan Dewan Perwakilan Rakyat. Keduanya harus menyetujui RUU sebelum diajukan ke presiden. Anggota DPR Indonesia dipilih setiap lima tahun, sedangkan anggota Kongres AS memiliki masa jabatan berbeda: senator dipilih setiap enam tahun dan anggota DPR setiap dua tahun. Proses legislasi di Indonesia dilakukan melalui pembahasan di komisi-komisi sebelum diputuskan dalam rapat paripurna